Evaluation of Supply Chain Performance A Manufacturing Industry Approach - Avelar-Sosa, Liliana; García-Alcaraz, Jorge Luis.; Maldonado-Macías, Aidé Aracely; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides some regional aspects considered by manufacturing firms in their decisions to gain competitiveness and have effects on the performance of their supply chains (SC). Some of the main aspects considered are: government's policies, fixed costs, the availability and quality of infrastructure services. This book also discusses the risks for the SC; based on a perception approach, some aspects studied are: demand, suppliers and production processes and how these are related to other elements of the SC. The authors use structural modeling to analyze the evaluation of some manufacturing practices and their impact on customer service satisfaction, agility and flexibility of the SC. The context of this study is immersed in the Mexican manufacturing industry of exportation, also known as maquiladora industry of Ciudad Juarez, México. This borderland is among the top 10 manufacturing Mexican cities. World class industries are located in this region and have been recognized aroundthe world for their competitiveness and high performance. Therefore, the methods and results exposed in this book may be valuable and useful for readers and researchers of the SC worldwide.
Competitiveness Aspects of Supply Chain -- Supply Chain Performance Factors -- Impact of Competitiveness on the Supply Chain Performance. .
Keywords: Industrial Management; Business logistics; Manufactures; Industrial Management; Supply Chain Management; Machines, Tools, Processes